Lithostratigraphy, biostratigraphy and chemostratigraphy of Upper Cretaceous and Paleogene sediments from southern Tanzania: Tanzania Drilling Project Sites 27-35 - Berrocoso, AJ; Huber, BT; MacLeod, KG; Petrizzo, MR; Lees, JA; Wendler, I; Coxall, H; Mweneinda, AK; Falzoni, F; Birch, H; Singano, JM; Haynes, S; et al. (2012)
The 2008 Tanzania Drilling Project (TDP) expedition recovered common planktonic foraminifera (PF), calcareous nannofossils (CN) and calcareous dinoflagellates with extraordinary shell preservation at multiple Cenomanian–Campanian sites that will be used for paleoclimatic, paleoceanographic, and biostratigraphic studies. New cores confirm the existence of a more expanded and continuous Upper Cretaceous sequence than had previously been documented in the Lindi and Kilwa regions of southeastern coastal Tanzania. This TDP expedition cored 684.02 m at eight Upper Cretaceous sites (TDP Sites 28–35) and a thin Paleocene section (TDP Site 27). TDP Sites 29, 30, 31 and 34 together span the lowermost Turonian to Coniacian (PF Whiteinella archaeocretacea to Dicarinella concavata Zones and CN Zones UC6a–9b), with TDP Site 31 being the most biostratigraphically complete Turonian section found during TDP drilling. A discontinuous section from the Santonian–upper Campanian (PF D. asymetrica to Radotruncana calcarata Zones and CN Zones UC12–16) was collectively recovered at TDP Sites 28, 32 and 35, while thin sequences of the lower Cenomanian (PF Thalmanninella globotruncanoides Zone and CN subzones UC3a–b) and middle Paleocene (Selandian; PF Zone P3a and CN Zone NP5) were cored in TDP Sites 33 and 27, respectively. Records of δ13Corg and δ13Ccarb from bulk sediments generated for all the Cretaceous sites show largely stable values through the sections. Only a few parallel δ13Corg and δ13Ccarb shifts have been found and they are interpreted to reflect local processes. The δ18Ocarb record, however, is consistent with Late Cretaceous cooling trends from the Turonian into the Campanian. Lithologies of these sites include thick intervals of claystones and siltstones with locally abundant, finely-laminated fabrics, irregular occurrences of thin sandstone layers, and sporadic bioclastic debris (e.g., inoceramids, ammonites). Minor lithologies represent much thinner units of up to medium-grained, massive sandstones. The %CaCO3 ...